2020
DOI: 10.1017/s0007114520003876
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of consumers of milk-alternative drinks v. cows’ milk: data from the UK National Diet and Nutrition Survey

Abstract: Milk is the main source of iodine in the United Kingdom (UK), however, the consumption and popularity of plant-based milk-alternative drinks is increasing. Consumers may be at risk of iodine deficiency as, unless fortified, milk alternatives have a low iodine concentration. We therefore aimed to compare the iodine intake and status of milk-alternative consumers to that of cows’-milk consumers. We used data from the UK National Diet and Nutrition Survey from Years 7-9 (2014-2017; before a few manufacturers fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
(44 reference statements)
0
26
3
Order By: Relevance
“…The authors estimated that 42% of the population total iodine intake was provided by the use of iodized salt and that this represented approximately 28% of the total salt used by the study participants. A more recent (2014–2017) UK survey in 2845 adults and children showed that the median UIC exceeded 100 µg/L only in regular consumers of cow milk, whereas the median UIC was lower in consumers of alternative types of milk [ 33 ]. Finally, the study of Trofimiuk-Müldner et al on children of school age ( n = 1000) and pregnant ( n = 300) and breastfeeding women ( n = 100) living in Poland showed that the mandatory sale of iodized salt to customers in the supermarkets markedly improved the iodine status in children but was not sufficient for pregnant and breastfeeding women [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors estimated that 42% of the population total iodine intake was provided by the use of iodized salt and that this represented approximately 28% of the total salt used by the study participants. A more recent (2014–2017) UK survey in 2845 adults and children showed that the median UIC exceeded 100 µg/L only in regular consumers of cow milk, whereas the median UIC was lower in consumers of alternative types of milk [ 33 ]. Finally, the study of Trofimiuk-Müldner et al on children of school age ( n = 1000) and pregnant ( n = 300) and breastfeeding women ( n = 100) living in Poland showed that the mandatory sale of iodized salt to customers in the supermarkets markedly improved the iodine status in children but was not sufficient for pregnant and breastfeeding women [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of dairy products by women of reproductive age could therefore be of concern because ‘milk and milk products’ currently contribute almost a third (32%) to daily iodine intakes for UK adults aged 19–64 years (Bates et al, 2020). A recent analysis of NDNS participants (aged 1.5 years and above) also reported that those exclusively consuming milk alternatives had a median UIC (79 µg/l) below the WHO cut‐off for iodine deficiency (100 µg/l), while those consuming cows’ milk (median UIC of 132 µg/l) were considered iodine sufficient (Dineva et al, 2020). Since the survey data were collected, some manufacturers have started to fortify plant‐based milk alternatives with iodine.…”
Section: Other Approaches To Identifying Healthier and More Sustainable Dietsmentioning
confidence: 99%
“…The low iodine content of unfortified milk alternative products, coupled with the positive trend in consumption, might be particularly concerning in countries with limited availability of iodised salt, such as the UK. Indeed, in a study that extracted data from the UK NDNS (between 2014 and 2017; when most milk alternatives on the market were not iodine-fortified), individuals who exclusively consumed milk-alternative drinks had a significantly lower iodine intake (94 vs. 129 μg/day) and iodine status (measured by the median urinary iodine concentration (UIC): 79 vs. 132 μg/L) than cow's milk consumers, suggesting that consumers of milk alternatives were not replacing the iodine elsewhere in the diet ( 87 ). The results are meaningful from a public health perspective, as those who consumed cow's milk were classified as iodine-sufficient according to the WHO criterion (median UIC 100 μg/L), whereas the exclusive consumers of milk alternatives were classified as iodine deficient.…”
Section: Dairy Nutrition Across the Life Course–future Research And I...mentioning
confidence: 99%